Paracoccidioides brasiliensis isolated from nine-banded armadillos (Dasypus novemcinctus) reveal population structure and admixture in the amazon basin - Bagagli, Eduardo [UNESP]; Matute, Daniel Ricardo; Garces, Hans Garcia [UNESP]; Tenório, Bernardo Guerra; Garces, Adalberto Garcia [UNESP]; Alves, Lucas Gomes de Brito; Yamauchi, Danielle Hamae [UNESP]; Hrycyk, Marluce Francisca; Barker, Bridget Marie; Teixeira, Marcus de Melo (MDPI, 2021)
Paracoccidioidomycosis is an endemic fungal disease to Latin America caused by at least five species-level genotypes of Paracoccidioides, named P. lutzii, P. brasiliensis (S1a and S1b populations), P. americana, P. restrepiensis, and P. venezuelensis. In this manuscript, we report on Paracoccidioides sp. sampling efforts in armadillos from two different areas in Brazil. We sequenced the genomes of seven Paracoccidioides isolates and used phylogenomics and populations genetics for genotyping. We found that P. brasiliensis and P. lutzii are both present in the Amazon region. Additionally, we identified two Paracoccidioides isolates that seem to be the result of admixture between divergent populations within P. brasiliensis sensu stricto. Both of these isolates were recovered from armadillos in a P. lutzii endemic area in Midwestern Brazil. Additionally, two isolates from human patients also show evidence of resulting from admixture. Our results suggest that the populations of P. brasiliensis sensu stricto exchange genes in nature. More generally, they suggest that population structure and admixture within species is an important source of variation for pathogenic fungi.
Keywords: Admixture; Amazon; Armadillos; Paracoccidioides; Paracoccidioidomycosis